Low-stakes assessments: An effective tool to improve marks in higher-stakes summative assessments? Evidence from commerce students at a South African university - Ontong, J. M. (Stellenbosch University, 2021)
The concept of practice makes perfect is often embedded in the decision to provide students with low-stakes formative and summative assessments with the intention of providing practice for higher-stakes summative assessments. The assumption is that participation in low-stakes formative and summative assessments will result in higher grades obtained in subsequent higher-stakes summative assessments. Using a quantitative approach, this study examined whether participation in low-stakes formative and summative assessments resulted in higher marks obtained in higher-stakes summative assessments. The findings of the study suggest that although in the majority of cases the participation of students in low-stakes formative or summative assessments resulted in higher marks obtained in subsequent summative assessments, an important planning consideration is the scope of the formative and summative assessments. The study found that when a low-stakes formative assessment does not cover the majority of the scope of the higher-stakes summative assessment, firstly, the participation percentage decreases significantly in comparison to other assessments that cover a larger portion of the scope of the following assessment. Secondly, the findings suggest that having a small, perhaps trivial, stake in terms of an assessment's contribution to final mark versus no stake has a significant impact on the students' participation levels, as well as the potential value added from participation in such assessments for future assessments. The findings also show that the quantity of low-stakes assessments does not necessarily need to be increased to increase the effectiveness of these interventions; instead, particular focus should be placed on ensuring that formative assessments cover the scope sufficiently of higher-stakes summative assessments if the intended purpose of these is to assist in improving marks in higher-stakes assessments. The findings suggest that the design of low-stakes formative and summative assessments are integral into the potential contribution these have on student performance in subsequent higher-stakes summative assessments.